1973
DOI: 10.1159/000197436
|View full text |Cite
|
Sign up to set email alerts
|

Detection by Immunofluorescence of Carcinoembryonic Antigen in Colonic Carcinoma, Other Malignant or Benign Tumours, and Non-Cancerous Tissues

Abstract: The indirect fluorescence method has been used to detect and localize carcinoembryonic antigen (CEA) in specimens of colonic carcinoma, other malignant or benign tumours, and non-cancerous tissues. The antigen was found in 39 specimens of colonic or rectal adenocarcinomas with a characteristic location at the apical pole of the cancerous cells. On the other hand, CEA was not detectable in two samples of anaplastic colonic carcinomas. Furthermore, CEA was occasionally found in some other digestive or non-digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

1975
1975
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 12 publications
(20 reference statements)
5
7
0
Order By: Relevance
“…We are in agreement with Bordes, Michiels and Martin (1973) in our localization of CEA in fresh, ethanol-fixed sections of apparently normal colonic mucosa from colonic cancer patients; however, we were unable to demonstrate CEA in any peritumoural, morphologically normal colonic mucosa that was only formalin-paraffin processed. This is most likely due to the low levels of CEA found in normal mucosa adjacent to colonic cancer (Khoo et al, 1973;Goldenberg et al, 1976), and our inability to detect CEA below 3 ,ug/g in formalin-fixed tissues (Goldenberg et al, 1976).…”
Section: Discussionsupporting
confidence: 91%
“…We are in agreement with Bordes, Michiels and Martin (1973) in our localization of CEA in fresh, ethanol-fixed sections of apparently normal colonic mucosa from colonic cancer patients; however, we were unable to demonstrate CEA in any peritumoural, morphologically normal colonic mucosa that was only formalin-paraffin processed. This is most likely due to the low levels of CEA found in normal mucosa adjacent to colonic cancer (Khoo et al, 1973;Goldenberg et al, 1976), and our inability to detect CEA below 3 ,ug/g in formalin-fixed tissues (Goldenberg et al, 1976).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, Lipkin and co-workers have described changes in the nucleic acid metabolism and proliferative capacity of the colonic epithelium in DMH treated mice (Thurnherr et al, 1973;Deschner, 1974) which are similar to those found in the human colonic mucosa adjacent to carcinoma and neoplastic polyps (Immondi, Balis and Lipkin, 1969;Deschner and Lipkin, 1970;Troncale, Hertz and Lipkin, 1971) and in familial polyposis (Lipkin, 1974). These changes may reflect a loss of suppressor genes and a regression of the cell to a more embryonic state, a hypothesis supported in the demonstration of embryonic specific antigens in malignant tumours (Gold and Freedman, 1965;von Kleist and Burtin, 1969;Stonehill and Bendich, 1970;von Kleist, 1971;Bordes, Michiels and Martin, 1973).…”
Section: Discussionsupporting
confidence: 56%
“…In some cells of MCT the immunofluorescence was seen around the cell surface, but was almost absent from the cytoplasm. The finding is quite similar to those shown in carcinoma or polyp of the colon, in which CEA is located on the luminal cell surface (Gold, Gold and Freedman, 1968; Kleist and Burtin, 1969;Denk et al, 1972;Burtin et al, , 1973Bordes, Michiels and Martin, 1973). In other cells, however, bright fluorescence was noted throughout the cytoplasm, exhibiting granulation.…”
Section: Discussionsupporting
confidence: 83%